Extraskeletal osteosarcoma with a highly malignant course - Simank, Hans-Georg; Welkerling, Heike; Bernd, Ludger; Ewerbeck, Volker (International orthopaedics, 1995)
A case of a highly malignant extraskeletal osteosarcoma is reported. Although biopsy is not considered necessary in cases of heterotopic calcification when the aetiology is known, malignancy should be suspected when the cause is questionable.